National Situation and Lingucist Consequences of Special Education in Biep in Alto Biobio Municipality, Chile; [Situación Nacional y Consecuencias Lingüicistas de la Educación Especial en Peib en la Comuna de Alto Biobío, Chile] - Loncon-Antileo, E (Emerson de Pietri, 2024)
There is currently an international framework and a national normative deployment that guides the education of original peoples around historical reparation, recognition and strengthening of their language. However, the current diagnosis identifies an academically inadequate, culturally unresponsive, and linguistically diglossic education. While the School Integration Program (SIP) seeks to promote learning achievements with cultural safeguards, international precedents problematize the cultural and linguistic unresponsiveness of the pathologizing assumptions and practices of special education applied in multicultural contexts. The absence of the Bilingual Intercultural Education Program (BIEP) and its actors in the discussion of sociolinguistic standards within the SIP restricts its possibilities of safeguarding and promoting cultural and linguistic rights. From the framework of the pathologization of non-dominant linguistic and communicational regimes as a sophisticated version of linguicism, this research used a mixed methodology to identify the national situation regarding the proportionality of special educational needs diagnoses -both in general and specifically associated with language and communication- between the population belonging and not belonging to original peoples, as well as to know in depth the linguistic situation, the uses of the diagnoses and the consequences of their implementation in Alto Biobio municipality. The unfavorable results in all the investigated aspects emphasize the need to address structures, ideologies and practices that continue to condition and promote subtractive and linguicist diagnostic and interventional practices, in order to distance ourselves from pathologizing paradigms towards linguistic and communicational diversification impulses in all areas of school practice. © (2024), (Emerson de Pietri). All rights reserved.